The importance of various fallows for changing the density of light-gray forest soil and yield productivity of plants in crop rotation - N. A. Komarova (Аграрная наука Евро-Северо-Востока)
The study was carried out in the Nizhny Novgorod region on light-gray forest soil in the period from 2011 to 2014. Factor А - fallows: bare fallows (unmanured, manure - 40 t/ha); green fallows (lupine, clover, rape), seeded fallows (clover, vetch oats, rape) with aftermath for green manure. Factor B - mineral fertilizers: phosphorus-potassium (Р90К90), nitrogen-phosphorus-potassium (N60Р90К90). During the research it has been established, that the highest biomass by natural moisture was obtained in green fallow of perennial lupine on the background of P90K90 and on the background of N60P90K90 - 43.42 and 46.05 t/ha respectively. Plowing it into the soil had a positive effect on the soil density. In the soil under winter wheat (renewal of vegetation) density value in the 0-10 cm layer was 1.27 g/cm3, which is 0.13 g/cm3 lower than for bare fallow. The decompressing effect of green clover fallow was preserved after wheat harvesting. The determination of soil density in oat plantings (the second crop after fallows) indicated a positive influence of the plowing organic mass of all studied fallow crops and the creation of optimal density for growth and development of oat (1.1-1.3 g/cm3). The green manure mass of meadow clover had the most significant decompressing aftereffect. The yield recording showed that the greatest amount of winter wheat grains was obtained from sowing it on green lupine fallow (on the P90K90 background - 3.05 t/ha, on the N60P90K90 background - 4.66 t/ha); and oat grains from manure aftereffect - 40 t/ha (3.80 and 4.50 t/ha respectively, depending on the background). The correlation analysis showed that the yield productivity of plants in crop rotation more depended on the amount of the plowed organic mass of fallow crops, than on the soil density. The density of soil, in turn, depended on the amount of organic matter, entering the soil with the fallow crops.